2018
DOI: 10.1063/1.5026112
|View full text |Cite
|
Sign up to set email alerts
|

Orientational ordering of lamellar structures on closed surfaces

Abstract: Self-assembly of particles with short-range attraction and long-range repulsion interactions on a flat and on a spherical surface is compared. Molecular dynamics simulations are performed for the two systems having the same area and the density optimal for formation of stripes of particles. Structural characteristics, e.g., a cluster size distribution, a number of defects, and an orientational order parameter (OP), as well as the specific heat, are obtained for a range of temperatures. In both cases, the clust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
10
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 72 publications
4
10
0
3
Order By: Relevance
“…As a result, a chain may wrap a few times around the sphere before merging into another chain (see bottom-left panel of Figure 6). This is similar to what was observed in a one-component system of particles interacting through a short-range attractive, long-range repulsive (SALR) potential [35]. The latter system was stripe-forming at low temperature; hence, when the particles were constrained to a spherical surface, a stripe may wrap around the sphere, as indeed observed.…”
Section: Same Size Of Dimers and Diskssupporting
confidence: 85%
“…As a result, a chain may wrap a few times around the sphere before merging into another chain (see bottom-left panel of Figure 6). This is similar to what was observed in a one-component system of particles interacting through a short-range attractive, long-range repulsive (SALR) potential [35]. The latter system was stripe-forming at low temperature; hence, when the particles were constrained to a spherical surface, a stripe may wrap around the sphere, as indeed observed.…”
Section: Same Size Of Dimers and Diskssupporting
confidence: 85%
“…Second, there coexists short-range attraction and longrange repulsion, judging from chain structures formed by droplets. Recently it was found that the mixture of short-range attraction and long-range repulsion can induce a chain-like lamellar structure in a confined geometry (Pȩkalski and Ciach, 2018). A peculiar feature of our dynamic system is, however, that the chains can be formed even in a low number density state as seen in Fig.…”
Section: Discussionmentioning
confidence: 83%
“…Несмотря на ожидаемое значительное влияние ограниченности системы [2,3] в целом, мало что известно о влиянии пространственных ограничений на упорядочение монослоев SALR-систем. Ламеллярные двумерные структуры в SALR-системе исследовались только в щелевой геометрии [1,4] или на поверхности сферы [5,6], на которой топологические дефекты обусловлены топологией системы. В трехмерных системах были изучены эффекты наложения периодического или замкнутого цилиндрического ограничения на гексагональную цилиндрическую фазу [7], показав стабильность спиральных структур, аналогичных тем, которые наблюдались для систем блоксополимеров [8].…”
unclassified
“…Ранее в работе [9] были рассмотрены основные состояния системы частиц с конкурирующими взаимодействиями в правильном шестиугольнике в виде концентрических колец. Однако в неограниченной системе при решеточной концентрации частиц, близкой к 0,5, при низких температурах существует фаза ламелей в виде параллельных полос [1,6], состоящих из двух заполненных и двух вакантных рядов. В данной работе рассматриваются условия существования такой фазы при наличии пространственного ограничения в виде правильного шестиугольника.…”
unclassified
See 1 more Smart Citation